A Quantitative Analysis of Organizational Citizenship Behavior and Its Impact on Employee Performance at PT Maju Bersama - Viona Kumalasari; Rianda Elvinawanty; Verawaty; Tiara Mastari Purba; Mukhaira El Akmal (Da'wa Faculty of Islamic State University Salatiga, 2025)
In the workforce, proactive behavior has rapidly developed into a standard practice. This guideline refers to an individual's ability to take initiative, act before problems arise, and adapt to changes, which can be reflected in employee performance. The aim of this study is to identify the relationship between Organizational Citizenship Behavior (OCB) and employee performance at PT Maju Bersama. The study used a sample of 105 employees from PT Maju Bersama. A quantitative approach was the research method applied. The analysis results showed that the Pearson correlation value obtained was 0.597, with a significance level (p-value) of 0.000 (p<0.05). These results indicate a significant positive relationship, suggesting a strong and meaningful connection between these variables. Additionally, the study noted that the coefficient of determination for the OCB variable towards performance was 0.356, indicating that OCB contributes 35.6% to performance.